2011
DOI: 10.1103/physreva.83.053603
|View full text |Cite
|
Sign up to set email alerts
|

Mode competition in superradiant scattering of matter waves

Abstract: Superradiant Rayleigh scattering in a Bose gas released from an optical lattice is analyzed with incident light pumping at the Bragg angle for resonant light diffraction. We show competition between superradiance scattering into the Bragg mode and into end-fire modes clearly leads to suppression of the latter at even relatively low lattice depths. A quantum light-matter interaction model is proposed for qualitatively explaining this result.PACS numbers: 03.75. Gg; 03.75.Hh; 42.50.Nn; 42.50.Gy The coherent n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…and, as a result, a complex nomenclature has evolved including the terms superradiance, superfluorescence, amplified spontaneous emission, mirrorless lasing, and random lasing [2, 4,[6][7][8][9], the distinctions among which we will not attempt to summarize here. The problem has recently seen renewed interest in the field of cold atoms [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This is partly because cold atoms provide a reproducible, easily characterized ensemble in which Doppler broadening effects are small and relaxation is generally limited to spontaneous emission.…”
mentioning
confidence: 99%
“…and, as a result, a complex nomenclature has evolved including the terms superradiance, superfluorescence, amplified spontaneous emission, mirrorless lasing, and random lasing [2, 4,[6][7][8][9], the distinctions among which we will not attempt to summarize here. The problem has recently seen renewed interest in the field of cold atoms [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This is partly because cold atoms provide a reproducible, easily characterized ensemble in which Doppler broadening effects are small and relaxation is generally limited to spontaneous emission.…”
mentioning
confidence: 99%
“…For example, they studied sequential scattering in superradiance from a Bose-Einstein condensate pumped by a two-frequency laser beam, which revealed that the frequency overlap between the end-fire modes related to different side modes plays an essential role in the dynamics of sequential superradiant scattering [90]. [91,92] studied the high-order momentum modes and mode competition in the superradiant scattering of matter waves. [93] studied superradiant scattering from a Bose-Einstein condensate using a pump laser incident at a variable angle and showed the presence of asymmetrically populated scattering modes.…”
Section: Bose-einstein Condensatementioning
confidence: 99%
“…The macroscopic coherent properties of ultra-cold atoms (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) are conducive to precise measurement. To make full use of the advantages of ultra-cold atomic coherence properties, one method is to reduce the manipulation time and another is to suppress the attenuation of coherence.…”
Section: Enhanced Resolution By Increasing Coherent Timementioning
confidence: 99%